Zanclea hicksoni Stepanjants 1972 ... - ÁLVARO L. PEÑA CANTERO (Zenodo, 2017)
Zanclea hicksoni (Stepanjants, 1972) (*) Corynidae Species B Hickson & Gravely, 1907: 16, pl. 3, fig. 17. Zanclea hicksoni —Peña Cantero et al., 2013: 741, figs 2g, 5e–f. Distribution. East Antarctic (Stepanjants 1979). In the Ross Sea, known from McMurdo (Hickson & Gravely 1907) and from Tethys Bay (Peña Cantero et al. 2013). ... : Published as part of ÁLVARO L. PEÑA CANTERO, 2017, Benthic hydroids (Cnidaria, Hydrozoa) from the Ross Sea (Antarctica) collected by the New Zealand Antarctic expedition BioRoss 2004 with RV Tangaroa, pp. 1-65 in Zootaxa 4293 (1) on pages 22-23, DOI: 10.11646/zootaxa.4293.1.1, http://zenodo.org/record/828475 ...